The Periplasmic 9.6-Kilodalton c-Type Cytochrome of Geobacter sulfurreducens Is Not an Electron Shuttle to Fe(III) - Lloyd, Jon R. (American Society for Microbiology, 1999)
Geobacter sulfurreducens contains a 9.6-kDa c-type cytochrome that was previously proposed to serve as an extracellular electron shuttle to insoluble Fe(III) oxides. However, when the cytochrome was added to washed-cell suspensions of G. sulfurreducens it did not enhance Fe(III) oxide reduction, whereas similar concentrations of the known electron shuttle, anthraquinone-2,6-disulfonate, greatly stimulated Fe(III) oxide reduction. Furthermore, analysis of the extracellular c-type cytochromes in cultures of G. sulfurreducens demonstrated that the dominant c-type cytochrome was not the 9.6-kDa cytochrome, but rather a 41-kDa cytochrome. These results and other considerations suggest that the 9.6-kDa cytochrome is not an important extracellular electron shuttle to Fe(III) oxides.